IMMUNOMORPHOLOGICAL FEATURES OF INFLAMMATORY BOWEL DISEASE AND RISKS OF MALIGNIZATION: LITERATURE REVIEW - Navruzov, S.N.; Navruzov, B.S.; Khakimov, A.M.; Rakhmonov, S.T.; Alieva, D.A.; Madaliev, A.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
The article provides a brief overview of modern scientific data on the occurrence of inflammatory bowel diseases, the currently existing theoretical foundations of etiopathogenesis and the mechanisms of their formation as a result of violations of the immunogenetic, morphological, microbiotic systems of the body.